The Central Negative Regulator of Flooding Tolerance, the PROTEOLYSIS 6 Branch of the N-degron Pathway, Adversely Modulates Salinity Tolerance in Arabidopsis - Suman Lamichhane; Jasper B. Alpuerto; Abigail Han; Takeshi Fukao (Plants, 2020)
Seawater intrusion in coastal regions and waterlogging in salinized lands are serious constraints that reduce crop productivity under changing climate scenarios. Under these conditions, plants encounter flooding and salinity concurrently or sequentially. Identification and characterization of genes and pathways associated with both flooding and salinity adaptation are critical steps for the simultaneous improvement of plant tolerance to these stresses. The PROTEOLYSIS 6 (PRT6) branch of the N-degron pathway is a well-characterized process that negatively regulates flooding tolerance in plants. Here, we determined the role of the PRT6/N-degron pathway in salinity tolerance in Arabidopsis. This study demonstrates that the prt6 mutation enhances salinity tolerance at the germination, seedling, and adult plant stages. Maintenance of chlorophyll content and root growth under high salt in the prt6 mutant was linked with the restricted accumulation of sodium ions (Na+) in shoots and roots of the mutant genotype. The prt6 mutation also stimulated mRNA accumulation of key transcription factors in ABA-dependent and independent pathways of osmotic/salinity tolerance, accompanied by the prominent expression of their downstream genes. Furthermore, the prt6 mutant displayed increased sensitivity to ethylene and brassinosteroids, which can suppress Na+ uptake and promote the expression of stress-responsive genes. This study provides genetic evidence that both salinity and flooding tolerance is coordinated through a common regulatory pathway in Arabidopsis.